Kerja Sama China-Djibouti dalam Djibouti International Free Trade Zone melalui Kerangka Foreign Aid and Donor Interest Model - Fenny Novita Rantepadang; Triesanto Romulo Simanjuntak; Novriest Umbu W. Nau (Pusat Riset dan Inovasi Nasional, 2025)
The China government’s provision of foreign aid to Djibouti illustrates a strategic shift from traditional development assistance to a tool for advancing national interests and consolidating geopolitical influence. This study explores how China utilizes foreign aid to secure geopolitical influence and pursues economic objective in the Horn of Africa. Employing a descriptive qualitative approach with secondary data sources and guided by the Foreign Aid and Donor Interest Model, this study finds that projects such as the Djibouti International Free Trade Zone (DIFTZ) and other infrastructure developments represent more than just economic cooperation, they are part of a broader strategic agenda to consolidate China’s presence in the region. These initiatives are predominantly carried out by China state-owned enterprises that not only sign major construction and development contracts but also import China workers to execute the projects. The findings suggest that China’s aid is interest-based, serving to establish economic networks, expand military reach, and secure crucial global trade routes.